AIRCRAFT FINANCIAL LEASING AGREEMENT - Polishchuk, Inna; Leuska, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study and analyse the legal nature of an aircraft financial leasing agreement and the peculiarities of its application in practice, highlighting the specifics of its subject matter, content, essential terms and conditions, and the subject matter of its parties in the aviation industry. Research methods: the study was conducted using general methods of cognition, analysis and synthesis, as well as special methods: formal-logical, formal-legal, structural-functional and comparative methods. Results: the author proves that an aviation financial leasing agreement is an extremely common type of economic and legal relations, the subject of which are aircraft objects transferred under the agreement by one party (the lessor) for exclusive use by the other party (the lessee) for a specified period of time, not less than the period for which 75% of the value of the leased object determined as of the date of the agreement is amortized, subject to payment of periodic lease payments. In this case, each party to the relationship satisfies its own interest. For a lessor, leasing an aircraft or other aviation facility is a profitable way to invest capital and a means of efficiently placing monetary assets. Aircraft owners can actively influence the aircraft leasing market and thereby expand their sales volumes. They also benefit from the possibility of receiving the full value of the leased aircraft with the help of intermediaries, which are usually leasing companies. As for the lessees, this is an opportunity to expand production capacity and upgrade their aircraft fleet without using borrowed capital or loans. Financial leasing is seen as a modern tool in the operations and development of many airlines both in Ukraine and globally, as it plays a crucial role in modernising production and increasing commercial profits, it is a flexible economic form that allows to meet the needs for aircraft use, and a financial leasing agreement significantly reduces the burden of bearing tax costs for the purchase of a new aircraft. Discussion: the priorities for expanding the institution of financial leasing through the conclusion of relevant agreements in the aviation sector will create new prospects for the development of the industry, rational use of funds of aviation enterprises, restoration of their activities in the war and post-war period both in Ukraine and abroad, and will intensify investment processes in the industry. Therefore, it is necessary to update the improvement of national legislation in the field of financial leasing and regulation of its agreements with the specifics of aircraft leasing, taking into account the peculiarities of their subject matter, subject composition, calculation and payment of lease payments, insurance premiums, etc.